Mucormycosis an added burden to Covid-19 Patients: An in-depth systematic review. Issue 11 (November 2022) - Shah, Naveed Nazir; Khan, Zaid; Ahad, Hashim; Elderdery, Abozer Y.; Alomary, Mohammad N.; Atwah, Banan; Alhindi, Zain; Alsugoor, Mahdi H.; Elkhalifa, Ahmed M.E.; Nabi, Showket; Bashir, Showkeen Muzamil; Yaqub, Tahir; et al.
Abstract: As of 25th July, 2022, global Disease burden of 575, 430, 244 confirmed cases and over 6, 403, 511 deaths have been attributed to coronavirus disease 2019 (COVID-19). Co-infections/secondary infections continue to plague patients around the world as result of the co-morbidities like diabetes mellitus, biochemical changes caused by Severe Acute Respiratory Syndrome Coronavirus-2 (SARS-CoV-2) especially significant elevation in free iron levels, immune suppression caused by SARS-CoV-2, and indiscriminate use of systemic corticosteroids for the treatment of severe COVID-19 disease. In such circumstances, opportunistic fungal infections pose significant challenge for COVID-19 disease therapy in patients with other co-morbidities. Although COVID-19-associated Mucormycosis (CAM) has been widely recognized, currently extensive research is being conducted on mucormycosis. It has been widely agreed that patients undergoing corticosteroid therapy are highly susceptible for CAM, henceforth high index of screening and intensive care and management is need of an hour in order to have favorable outcomes in these patients. Diagnosis in such cases is often delayed and eventually the disease progresses quickly which poses added burden to clinician and increases patient load in critical care units of hospitals. A vast perusal of literature indicated that patients with diabetes mellitus and those with other co-morbidities might be highly vulnerable to develop mucormycosis. In the present work, the case series of three patients presented at Chest Disease Hospital Srinagar, Jammu and Kashmir infected with CAM has been described with their epidemiological data in supplementary section. All these cases were found to be affected with co-morbidity of Diabetes Mellitus (DM) and were under corticosteroid therapy. Furthermore, given the significant death rate linked with mucormycosis and the growing understanding of the diseases significance, systematic review of the literature on CAM has been discussed and we have attempted to discuss emerging CAM and related aspects of the disease.